ANALISIS IMPLEMENTASI KEBIJAKAN INTEGRASI LAYANAN PRIMER TERHADAP PENINGKATAN AKSES LAYANAN KESEHATAN DI PUSKESMAS CIWANDAN - Hartana, Arief Dharma; Subuh, Subuh; Purnamasari, Ratih (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
The Primary Service Integration Policy is an effort to coordinate the integration of primary health services into a single, comprehensive unit that aims to improve access to health services in the community, especially promotive and preventive services, especially at the UPTD Ciwandan Health Center, Cilegon City. This study aims to analyze the implementation process of the Primary Service Integration policy towards improving access to health services at the UPTD Ciwandan Health Center, Cilegon City in 2024. The focus of this study is to identify challenges, obstacles, and opportunities for improvement in the process of increasing access to services.This study uses a mixed-methods approach through questionnaires and in-depth interviews, combining quantitative analysis of Primary Care Integration service data. Quantitative data were analyzed descriptively, while qualitative data were analyzed thematically. The research sample consisted of 99 respondents consisting of policy makers, policy implementers, and policy recipients. The collected data will be analyzed using descriptive statistics to describe the pattern of integrated services, while thematic analysis will be applied to interviews to uncover problems that occurred during the implementation of Primary Care Integration services regarding access to health services. 99 respondents knew about the Integration of Primary Services implemented at the UPTD Ciwandan Health Center, the majority of respondents (93.93%) assessed that the Integration of Primary Services was running well, the highest result was in ease of service (46.46%), while ease of access to services (21.21%).  The implementation of the Primary Service Integration (ILP) health service policy has been carried out well by the UPTD Ciwandan Health Center throughout 2024 and has provided results in its implementation such as ease of service and ease of access to services, which of course in the implementation process has obstacles and several shortcomings that need to be corrected. ABSTRAKKebijakan Integrasi Layanan Primer adalah suatu upaya untuk koordinasi penyatuan pelayanan kesehatan primer menjadi satu kesatuan secara menyeluruh yang bertujuan untuk meningkatkan akses pelayanan kesehatan dimasyarakat khususnya promotif dan preventif khususnya di UPTD Puskesmas Ciwandan Kota Cilegon. Penelitian ini bertujuan untuk menganalisis proses implementasi kebijakan Integrasi Layanan Primer terhadap peningkatan akses layanan Kesehatan di UPTD Puskesmas Ciwandan Kota Cilegon Tahun 2024. Fokus penelitian ini adalah mengidentifikasi tantangan, hambatan, serta peluang perbaikan dalam proses peningkatan akses layanan. Penelitian ini menggunakan pendekatan pendekatan campuran (mixed-methods) melalui kuisioner dan wawancara mendalam, dengan menggabungkan analisis kuantitatif dari data pelayanan Integrasi Layanan Primer. Pada data kuantitatif dianalisis secara deskriptif, sedangkan data kualitatif dianalisis secara  tematik. Sampel penelitian ada 99 responden terdiri dari pemberi kebijakan, pelaksana kebijakan dan penerima kebijakan. Data yang dikumpulkan akan dianalisis menggunakan statistik deskriptif untuk menggambarkan pola pelayanan teritegrasi, sedangkan analisis tematik akan diterapkan pada wawancara untuk mengungkap masalah yang terjadi selama pelaksanaan pelayanan Integrasi Layanan Primer terhadap akses pelayanan Kesehatan. Sebanyak 99 responden memgetahui tentang Integrasi Layanan Primer yang di implementasikan di UPTD Puskesmas Ciwandan, mayoritas reponden (93,93 %) menilai Integrasi Layanan Primer sudah berjalan baik, hasil tertinggi pada kemudahan layanan (46,46%), sedangkan kemudahan akses layanan (21,21%). Implementasi kebijakan pelayanan kesehatan Integarasi Layanan Primer (ILP) telah dilaksanakan dengan baik oleh UPTD Puskesmas Ciwandan sepanjang tahun 2024 dan memberikan hasil pada penerapannya seperti kemudahan layanan juga kemudahan akses layanan, yang tentunya dalam pada proses penerapan memiliki hambatan dan beberapa kekurangan yang perlu diperbaiki..